2012
DOI: 10.2298/sos1203341b
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nano-TiO2 addition on the properties of mullite-zirconia composites prepared by slip casting

Abstract: The mullite-zirconia composites were prepared by reaction-sintering of alumina and zircon powder. Besides, the slip casting method was employed for fabrication of these composites. Then, the effect of nano-TiO2 addition on the properties of these composites was investigated and the results were compared with micro-sized TiO2. Hence, the physical properties, phase composition, flexural strength and microstructure of these composites after firing at 1600°C were studied. The results showed that the flexural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…It has been reported that TiO 2 is a good mineralizer for promoting the crystallization of the MA and A 3 S 2 . In addition, TiO 2 was frequently employed to enhance the sintering of Al 2 O 3 ceramics through the formation of Al 2 O 3 ‐TiO 2 solid solution .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that TiO 2 is a good mineralizer for promoting the crystallization of the MA and A 3 S 2 . In addition, TiO 2 was frequently employed to enhance the sintering of Al 2 O 3 ceramics through the formation of Al 2 O 3 ‐TiO 2 solid solution .…”
Section: Introductionmentioning
confidence: 99%
“…The addition of TiO 2 to mullite-zirconia composites prepared from different alumina sources leads to change of reaction sintering, densification and microstructure which can alternately change the formation temperature and retention of tZrO 2 phase in these composites [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The mullite-zirconia composites containing different amounts of micro-and nano-TiO 2 particles were prepared by reactionsintering of alumina and zircon powder by other authors using slip casting as shaping method [23]. Then, the physical properties, phase composition, flexural strength and microstructure of these composites were finally evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Este conjunto de cualidades hacen de este cerámico un material de gran interés para aplicaciones en usos de alta tecnología en condiciones estructurales y se considera un material adecuado para su uso en electrónica [1,11], así como en fabricación de espumas cerámicas a partir de pastas refractarias para someterlas a trabajos de alta temperatura [12], en aplicaciones como aislantes térmicos, soportes para catalizadores, filtros, quemadores de combustión de gases, materiales estructurales livianos y biocerámicos [13,14]. Pero ante toda la diversificación de aplicaciones, la mullita al ser un material cerámico presenta alta fragilidad debido a su baja tenacidad a la fractura; es decir, es un material susceptible a falla mecánica por agrietamiento cuando es sometido a esfuerzos mecáni-cos. En este sentido se han realizado investigaciones en busca del incremento de esta propiedad mecánica y se ha encontrado que la incorporación de partículas metálicas y cerámicas en la matriz de materiales cerámi-cos han mejorado esta propiedad [3, [15][16][17][18]. En particular en algunas investigaciones principalmente donde el refuerzo de la matriz cerámica es metálica como Ag, Ti, Ni, Co, Cu fabricadas por molienda de alta energía han mostrado resultados favorables no solo en el incremento de la tenacidad a la fractura si no también cambios en la microestructura y dureza [15,[19][20][21], también en estudios de alúmina y mullita reforzadas con metales se han reportado comportamientos de naturaleza eléctrica [20,22].…”
unclassified
“…Pero ante toda la diversificación de aplicaciones, la mullita al ser un material cerámico presenta alta fragilidad debido a su baja tenacidad a la fractura; es decir, es un material susceptible a falla mecánica por agrietamiento cuando es sometido a esfuerzos mecáni-cos. En este sentido se han realizado investigaciones en busca del incremento de esta propiedad mecánica y se ha encontrado que la incorporación de partículas metálicas y cerámicas en la matriz de materiales cerámi-cos han mejorado esta propiedad [3, [15][16][17][18]. En particular en algunas investigaciones principalmente donde el refuerzo de la matriz cerámica es metálica como Ag, Ti, Ni, Co, Cu fabricadas por molienda de alta energía han mostrado resultados favorables no solo en el incremento de la tenacidad a la fractura si no también cambios en la microestructura y dureza [15,[19][20][21], también en estudios de alúmina y mullita reforzadas con metales se han reportado comportamientos de naturaleza eléctrica [20,22].…”
unclassified